Protective Effects of Sesamin on Cytoxan-Induced Spermatogenesis Dysfunction by Regulating RNF8-ubH2A/ubH2B Pathways in Male Mice - Hai, Dong-Mei; Ren, Jia-Wei; Chi, Yan-Nan; Ye, Rui-Juan; Liu, Ning; Ma, Lin; Lan, Xiao-Bing; Wu, Jing; Yu, Jian-Qiang; Yang, Jia-Mei (Frontiers in Pharmacology, 2021)
Most of the clinically infertile patients show spermatogenesis dysfunction. Cyclophosphamide, as an anticancer drug, can induce spermatogenesis dysfunction. Sesamin is the main bioactive component of natural lignans in sesame. It is abundant in sesame oil and has strong biological activities such as antioxidant, antibacterial, and hypoglycemic properties. By establishing the model of spermatogenic dysfunction induced by cyclophosphamide in male mice and then feeding sesamin (50, 100, and 200 mg/kg) for 2 weeks, we proved that sesamin can improve the reproductive organ damage induced by cyclophosphamide and increase the number and activity of sperms. Sesamin can resist cyclophosphamide-induced sperm nuclear maturity and DNA damage by increasing the expression levels of histones H2A and H2B in the testis. In addition, sesamin can improve the ubiquitination of histones regulated by RNF8 to protect the testis. In conclusion, these results suggest that sesamin can improve spermatogenic dysfunction induced by cyclophosphamide, which may be mediated by ubiquitination of histones.